THE APPLICATION OF TREFFINGER LEARNING MODEL IN IMPROVING STUDENTS’ MATHEMATICAL COMMUNICATION SKILL AND THEIR CONFIDENCE - Nurjanah, Enung Sopiyah (PRISMA, 2019)
Mathematics is considered as one of very important subjects in educational field. This can be proved by its lesson hour number at school, which is very large number. However, some think mathematics is very hard and boring for its uninteresting learning method. In attempt to eliminate this assumption, Treffinger model, as one of so many methods with their respective advantages, may be considered to be used. This model consists of three core steps, namely understanding challenge, generating ideas, and preparing for action. This study used quasi-experiment as its research method. The population of this study was all junior high school level students in Cianjur regency, meanwhile the sample of this study was 32 students of VIII E as the experimental class and 32 students of VIII G as the control class. The data obtained was then analyzed using the parametric and non-parametric statistical computation. The result of the data analysis showed that there were some improvements in experimental class students’ mathematical communication skill and their confidence in learning mathematics compared to those in control class which used conventional learning model as the treatment. The result also showed that there was an quite high association between students’ mathematical communication skills on the criteria of high enough. Lastly, the result also showed that there was an association between students’ communication skill quality and their confidence on the level of high criteria. Keywords: Treffinger, mathematical communication, confidence